UI/UX Redesign of SH-UPI App Using Design Thinking Framework - Fuada, Syifaul; Setyowati, Endah; Restyasari, Nissa; Heong, Yee Mei; Hasugian, Leonardi Paris (Society of Visual Informatics, 2024)
The rise of smart home technology has significantly impacted people’s behavior and lifestyle, especially when controlling household electronics remotely. Smart homes have become increasingly commoditized in the last decades, resulting in several vendors offering various commercial products and their variants. Universitas Pendidikan Indonesia (UPI) has created the smart home platform “SH-UPI,” which includes the Smart LED Bulb RGB. The platform’s mobile app can be downloaded from the Play Store or the official website (www.sh-upi.com). The SH-UPI is one of Indonesia's leading smart homes that adopted Internet-of-Things (IoT). However, customers have reported issues with the app’s user interface (UI) and user experience (UX), prompting a redesign to address these concerns and stay competitive. This study employs the design thinking method of empathizing, defining, imagining, prototyping, and testing. The define stage to prototype stage resulted in a newly designed prototype for the SH-UPI app. Testing involved evaluating the prototype using metrics like the User Experience Questionnaire (UEQ) and System Usability Scale (SUS). The test results showed an increase in the UEQ parameter value, exceeding the initial average scores of -0.8 to 0.8. Additionally, there was an improvement compared to benchmark scores, which initially ranged from below average to poor but now range from above average to excellent. The SUS score also improved, rising from 59.75 (grade D) to 83.625 (grade A). The findings of this study can be a valuable resource for developing SH-UPI apps with significantly enhanced UI/UX.